Peranti kohesi dalam wacana tulis siswa: Perkembangan dan kesalahannya - Ghufron, Syamsul (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
The aim of the study was to describe the cohesive devices found in students’ written discourse, along with their development and usage errors. The data were gathered from students’ writing products of 3rd, 4th, and 5th graders at SDN Baratajaya, Surabaya, using observation and tests as research instruments. The results show that all elementary students’ written discourses (Grades 3, 4, and 5) apply cohesive devices. The cohesive devices most widely used in their written discourse are conjunctions, lexical synonymy, and grammatical ellipsis. The findings illustrate not only the development of cohesive device usage, as reflected in the percentages of conjunctions, repetition, and synonymy in students’ written discourses, but also the description of cohesive device errors through the use of conjunctions, ellipsis, substitution, reference, and repetition.